Antimicrobial stewardship in hospitals in Latin America and the Caribbean: a scoping review - Jennifer Hegewisch-Taylor; Anahí Dreser-Mansilla; Julián Romero-Mónico; Gabriel Levy-Hara (Pan American Health Organization, 2020)
Objectives. To examine published antimicrobial stewardship (AMS) initiatives in hospitals in Latin America and the Caribbean (LAC) in order to characterize AMS terminology usage, geotemporality, and elements of structure (human resources), process (interventions), and outcomes, and to set priority areas for improving AMS reporting. Methods. This was a scoping review that searched PubMed, LILACS, EMBASE, and 12 other databases, along with a manual search for academic and grey literature to identify documents on AMS initiatives in hospitals in 33 countries of LAC, up to August 2019. Keywords included 'antibiotic' or 'antimicrobial' AND 'stewardship, policy, strategies, management, control, rational use, appropriate use, surveillance, or interventions' and 33 country names. Results. Selected articles totalled 147 studies published in 1985 - 2019; of those, 22% used 'antimicrobial stewardship' in the title. Eighteen countries published AMS hospital initiatives, one-half of which were implemented in capital cities. Brazil, Argentina, Colombia, Cuba, Mexico, and Chile, in descending frequency, made up > 59% of published initiatives. Educational interventions were the most frequently reported, followed by persuasive and restrictive strategies. Antimicrobial consumption was the most common outcome measure reported. About one-third of the studies (35%) referred to baseline measures-only in preparation for AMS interventions. Fifty-nine studies from 6 countries reported AMS comprehensively, using structure, process, and outcome (SPO) elements. Conclusions. Published hospital AMS initiatives have increased over time and have expanded across LAC. However, more programs need to be developed. Complete reporting of SPO elements is imperative to evaluating and replicating AMS actions.